Entrance and lettering, Court View - Ghosh, Ayan (Jio Institute, 2023)
Court View, 126 Maharshi Karve Road, Churchgate. Court View was named after the Bombay High Court which is visible across the Oval Maidan. Architects Maneckji Dalal and Merwanji Bana & Co. designed Court View with additional designs by Gajanan Babu Mhatre, who was brought on as consultant at the later stages.